ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI SAWAH DI DESA SEPANG KECAMATAN PAMPANGAN KABUPATEN OKI - Randika, Reki; Sidik, Muhamad; Peroza, Yulliah (Universitas Muhammadiyah Palembang, 2021)
This study aims to determine the analysis of the factors that influence the production of lowland rice in Sepang Village, Pampangan District, Ogan Komering Ilir Regency. This research was carried out in Sepang Village, Pampangan District, Ogan Komering Ilir Regency from June to July 2021. The research method used was a survey method, namely conducting a thorough observation of rice production farming. The sampling method in this study is the purposive sampling method. The total population of rice farmers in Sepang Village, Ogan Komering Ilir Regency, is 1,014 samples and 91 respondents. The data collection method used in this study was direct observation and interviews with respondents, using tools in the form of a list of previously prepared questions and data obtained from relevant institutions related to this research.The results showed that based on the results of testing the productivity variable (X) had a positive and significant effect on income (Y). This means that Ha is accepted and H0 is rejected. The number of workers, land area, use of seeds, use of urea fertilizer and use of insecticides, simultaneously have a significant effect on increasing rice production in Sepang Village, Ogan Komering Ilir Regency. The amount of income of rice farmers in the study area is an average of Rp. 5.993.746 per planting season.